Penerapan Ekonomi Sirkular dalam Proses Pengelolaan Sampah oleh Bank Sampah Mekar Sari - Ciek Julyati Hisyam; Mayang Puti Seruni; Agnes Clara Nainggolan; Aryo Anargya Hakim Putra; Chieka Aisyah Kinanti; Ghifari Shafa Darmawan; Riyan Adhitya Pratama; Zakiyah Rodja (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Waste management in urban areas such as South Jakarta remains a major challenge, particularly at the household level. This study aims to examine the role of Bank Sampah Mekar Sari in implementing circular economy principles through community-based waste management. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The findings show that Bank Sampah Mekar Sari functions not only as a collection point for inorganic waste but also as a center for educating and empowering residents to sort and manage waste sustainably. The practices observed, such as household-level sorting, partnerships with recycling partners, and material reuse, reflect the core principles of the circular economy. In addition, collaboration among community members, local government, and the private sector contributes to the development of a participatory waste management ecosystem. This study recommends replicating similar models in other regions and highlights the importance of regulatory and institutional support in strengthening local waste management systems.